Dr. Neelima Jeychandran and Prof. Dr. Clarissa Vierke on the circulation of objects in the Indian Ocean - Jeychandran, Neelima; Vierke, Clarissa (Cluster Conversations, 2024)
Neelima Jeychandran is an Assistant Professor of African Visual Culture in the Department of Art History at Virginia Commonwealth University, Qatar. In this episode, she talks with her host Clarissa Vierke (Professor of Literatures in African Languages at the ⁠University of Bayreuth⁠) about Jeychandran's work on oceanic crossovers and material histories of West and East Africa and western India. She is an ethnographer, editor, scholar, and was a fellow at the Africa Multiple Cluster of Excellence from May until July 2024.